Toxicity of glyphosate on snow pea (Pisum sativum) in sandy-loam soil with a bacterial consortium - Cruz-Inca, Kevin (2025)
Introduction. Glyphosate (GLI) is a widely used herbicide that, when applied in excess, can affect bothbroadleaf weeds and crops. Plant growth-promoting bacteria may enhance crop resistance and protection against GLI effects. Objective. To evaluate GLI toxicity on the root, stem, and combined root + stem of Pisum sativum in sandy loam soil, in the presence of Ochrobactrum anthropi and Pseudomonas aeruginosa, both individually and as a bacterial consortium composed of both microorganisms. Materials and methods. The experiment was conducted in a greenhouse in Lima, Peru, using a completely randomized design with 32 treatments. Soil was mixed with GLI and subjected to edaphological analysis. Four treatments served as controls, twelve contained soil with O. anthropi and P. aeruginosa individually and on their bacterial consortium, and sixteen treatments included P. sativum. Results. P. sativum exposed to 8.71 mL L-1 and 17.42 mL L-1 of GLI showed a significant growth reduction, particularly in freshstem and root biomass. However, bacterial consortium reversed this effect and improved growth. GLI altered soil pH and electrical conductivity, while organic matter remain unchanged. Soil available potassium increased with GLI, but bacterial presence reduced this effect. Available phosphorus increased in treatments combining P. sativum and GLI at 17.42 mL L-1. Conclusions. Higher GLI concentrations negatively impacted P. sativum stem and root growth, but bacterial inoculation attenuated these effects and modified soil properties. These findings highlight the relevance of the interaction between herbicide, microorganisms, and soil parameters in agriculture.